Origin of dissolved organic carbon under phosphorus-limited coastal-bay conditions revealed by fluorescent dissolved organic matter - Kim, Jeonghyun; Song, Byung-Chan; Kim, Tae-Hoon (Frontiers in Marine Science, 2022)
To determine the origins of dissolved organic carbon (DOC) in a bay of volcanic Jeju Island, where the discharge of fresh groundwater (FGW) is dominant, we measured fluorescent dissolved organic matter (FDOM) and implemented a parallel factor analysis (PARAFAC). The PARAFAC model identified three humic-like components (FDOMH) and one protein-like component (FDOMP). DOC was extremely deficient in the FGW (35 ± 13 μM) and positively correlated with salinity in the coastal environment, indicating oceanic DOC contribution. The FDOMP pattern was similar to that of DOC, suggesting that marine biological production is a primary DOC source in this region. Particularly, significant FDOMP correlations in the coastal waters with the fluxes of dissolved inorganic phosphorus (DIP; R2 = 0.31) and dissolved silicon (R2 = 0.46) from the FGW demonstrated that in situ biological production is facilitated by FGW-borne nutrient addition. However, the absence of a correlation between the fluxes of dissolved inorganic nitrogen (DIN) and FDOMP (R2 <0.01) indicated that anthropogenic DIN is not essential for DOC production under the P-limited nutrient conditions and diatom-dominant conditions prevailing on the coastal Jeju Island. Here, we calculated the potential capacity of carbon fixation by marine biological activity based on the Redfield ratio of carbon and phosphorus with DIP fluxes. The flux accounts for approximately 2% of the terrestrial carbon uptake in South Korea. Therefore, optical properties of FDOM may be good indicators of coastal DOC origin, and nutrient speciation may be linked to the carbon cycle.